LONGING FOR JUSTICE: TWENTY-TWO YEARS-LONG CHURCH CONSTRUCTION CONFLICT RESOLUTION IN SEMARANG - Nugroho, Adrianus Bintang Hanto; Wijaya, Emilia Metta Karunia (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
Christian places of worship have become the most frequently targeted places of worship in Indonesia, with the reported religious discrimination numbers increasing over the past several years, according to reports from the Setara Institute. One of the prominent cases is a prolonged opposition and rejection of the GBI Tlogosari church construction, which lasted from 1998 to 2020. Throughout this period, the involved parties attempted to settle the conflict through various approaches to conflict resolution. This research aims to explore the conflict resolution efforts made particularly by the GBI Tlogosari. Data was collected from diverse sources, including reports from civil society organizations, and analyzed using a qualitative descriptive method. After enduring minoritization and experiencing a situation of de facto rightlessness for more than twenty years, the GBI Tlogosari congregations finally achieved its objective of establishing a church building. Although the initial negotiations with lower-level government officials denied their right to freedom of religion and belief, the subsequent mediations with higher-level government officials proved to be successful. The mediation approach employed by the lower-level officials largely relied on power and authority, whereas the higher-level officials tended to integrate both rights-based and interests-based models.Keywords: minoritization, religious discrimination, freedom of religion and belief, conflict resolution